URBAN INFORMAL SECTOR MOBILITY: SOCIOECONOMIC ANALYSIS OF STREET VENDORS IN THE SUDIANG SPORTS COMPLEX AREA, BIRINGKANAYA SUB-DISTRICT, MAKASSAR CITY - Asmirah, Asmirah (Indonesian Journal Of Economy Studies, 2023)
The population growth rate in a region has an impact on the growth rate of the workforce in that area. In such a situation, there is an increase in economic activities at the regional, national, and even global levels. Street vendors, also known as 'Pedagang Kaki Lima' (PKL), are one form of informal sector economic activity that is on the rise. There is a connection between population growth rate, labor force participation, and job availability. Job opportunities in the formal sector are not proportional to the number of job seekers, motivating them to create their own jobs as street vendors. This analysis focuses on the mobility of the urban informal sector: A socioeconomic analysis of street vendors in the GOR Sudiang area of Makassar City. The analysis specifically looks at the patterns of adaptation of street vendors in the digital era and the strategies employed by them for business sustainability. The research concentrates on street vendors operating on the outskirts of the GOR Sudiang area and employs a qualitative research approach. Informants for the research were selected using purposive sampling, with a total of five informants initially identified. A snowball sampling technique was also used, adding three more informants when certain questions required additional input. Data collection techniques included observation, in-depth interviews, and documentation. The research findings indicate that: 1) Street vendors have adopted online transaction technologies; 2) They have formed social groups with economic goals through 'arisan' activities. They are capable of adapting to new locations, new jobs, and meeting new people by maintaining a sense of togetherness, mutual assistance, and trust. They can conduct online transactions and collaborate with online transportation services. 'Arisan' groups are formed because they provide a flexible and adaptive platform for discussing various issues, including those related to street vending activities.